SYNTACTIC AND SEMANTIC FEATURES OF VERBS OF POSSESSION IN ENGLISH AND IN VIETNAMSE / Tran Thi Thu Hang; NHDKH Dr Dang Ngoc Huong - Tran, Thi Thu Hang
As the title indicates this study is aimed at investigating syntactic and semantic features of verbs of possession in English and in Vietnamese. The study is aimed at three point: (1) the syntactic and semantic features of possession in English and in Vietnamese (2) finding the similarities and differences of verbs of possession in English their Vietnamese equivalents and (3) providing some recommendation for the teaching and learning as well as translation of verbs of possession into the target language. This study was designed as a descriptive survey method, comparative and contrastive method. According to the data analysis, the result of the study show that each type of verbs in all the syntactic and semantic features as has been described in grammar books. In general, English verbs of possession and their Vietnamese collected indicate that the structure of sentences consisting of verbs of possession in English is different from that in Vietnamese. Besides the word forms of verbs of possession in English sentences which have to change according to grammatical rules, or situation in each sentence. These features are not found in Vietnamese sentences. English employs different structures to express different meanings whereas Vietnamese uses words as major means to construct sentences. the study not only supplies some implications to language teaching, learning as well as translating but also raises language users’ awareness of the differences between verbs of possession so that they can use them exactly and be successful in their real life communication in English